Manifestation of cultural identity(s) in an Iranian English language Literacy classroom: a critical discourse analysis - Khadijeh Aghaei,; Koo, Yew Lie; Noorizah Mohd Noor, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
English language Literacy education has recently focused attention on cultural identity(s). In these studies, cultural identities are defined as a significant “source of meaning and experience” constructed by and connected to the social context of the external world. More precisely, cultural identities are constructed by increasingly complexities of what construct literacy and multi literate practices in 21 century as a constantly changing socially and culturally diverse, globalized and technological era. This view can open a new horizon to English language literacy education in the new era which is supposed to go beyond merely 4 -skill dominant pedagogical orthodoxy. The current study as a qualitative case study framed in New London Group focuses on how literacy practices and consequently cultural identities are constructed in an Iranian EFL classroom. To do so, we applied a critical classroom discourse analysis as the main technique of data collection. Results of this study can enrich the research literature in new literacy studies in which EFL contexts are still less visible.